Effect of Progressive Muscle Relaxation Therapy on Blood Pressure in Hypertension Sufferers in Pantoloan Health Center Area Huntara - Yulianus Sudarman; Iwan Iwan; Amyadin Amyadin (Universitas Muhammadiyah Palu, 2023)
Background: Hypertension is an increase in blood pressure both diastolic and systolic which disappear or persist with increasing blood pressure -> 140/90 mmHg. In Indonesia reaching 32% of the total population, hypertension sufferers amounting to 15 million but only 4% are under controlled hypertension Pantoloan Puskesmas data with 2018 new cases based on visits to services totaling 218 cases. The purpose of this study was to determine the effect of providing progressive muscle relaxation therapy on blood pressure in hypertensive patients in the Pantaraan Puskesmas working area. Method: This type of analytic research, true experimental design with pretest- posttest control design. The population of hypertension sufferers in Pantoloan is 218 people. The sampling technique of this study was purposive sampling, as many as 14 patients with hypertension were divided into 2 groups, namely therapy and control. Result: Paired t-test results are P value = 0.005 and 0.047 for the morning and P Value = 0.001 and 0.000 in the afternoon (<0.05) so that statistically there is an influence on the provision of progressive muscle relaxation therapy in patients with hypertension in Huntara region Pantoloan Puskesmas work. The conclusion in this study is that there is a significant effect of progressive muscle relaxation therapy on blood pressure in patients with hypertension in the Pantoloan Puskesmas Work Area. Conclusion: Suggestions for puskesmas are expected to be useful as an alternative to providing non-pharmacological therapy to hypertensive patients in addition to ongoing medical therapy